Penerapan Green Accounting dalam Upaya Pencegahan Pencemaran Lingkungan Limbah Produksi Krupuk Pati - Pandin, Maria Yovita R. Pandin; Adiati Trihastuti, Rr; Bayu Ramadhan, Charisma; Rahmawati, Novita (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to describe and explain the application of green accounting in helping efforts to prevent environmental pollution from starch cracker production waste. The facts in this research are based on the fact that the majority of home industry players pay little attention to the impact of waste on the surrounding environment and are less concerned about environmental pollution problems. Descriptive qualitative methods were used, where data collection was carried out in the form of field research, documentary research and library research. This research method uses qualitative, data collection is carried out by in-depth interviews, documenting reports that are directly related to environmental costs, then the last is observing the environmental conditions of the village to be studied. The results show that the low level of environmental awareness from the survey shows that there are still many people who have a low level of environmental awareness. They may not be aware of the negative impact of liquid waste produced by their activities on the surrounding environment.